Assessment of factors contributing to maintenance problems in higher institutions in Niger State, Nigeria - Okosun, B. O.; Olagunju, R. E. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Maintenance generators degrade the quality standard of a building and if left unattended will definitely cause more damages and in the long–run, costly repairs. Maintenance staff are sometimes faced with the challenges of detecting the exact source of maintenance problems in buildings, this necessitated a research to assess factors that contribute to maintenance problems in higher institutional buildings and propose best practice criteria for effective maintenance management. Method of data collection was via questionnaire. The results from the data of the descriptive analysis were presented using Relative Important Index (RII). 101 questionnaires were administered with a response rate of 96.04%. Findings from the study revealed human/user factors and management related factors as the most contributory to maintenance problems of the studied higher institutions. The least considered best practice criteria was computerized maintenance management system (CMMS) with a mean score of 2.82. Several higher institutions maintenance departments lack a computerized work system. This may not be surprising giving the phobia many people still have for computers. Almost all the maintenance departments lack qualified computer personnel to operate an effective CMMS. This study will help the higher institution management tackle the identified major problems that results in deterioration of building facilities.